Critical assessment of a wide-spread method for estimating energy expenditure during accelerated running based on positioning tracking systems - Fuchs, P. X.; Fuchs, P.; von Duvillard, S. P.; Wagner, H.; Shiang, T. Y. (Journal of Sport and Health Science, 2022)
An innovative method for estimating energy cost is to consider accelerated/decelerated running on flat terrain metabolically equivalent to uphill/downhill running at constant speed.1, 2, 3 In this method, the authors estimated an acceleration-dependent body slope. That slope corresponded to a given terrain slope during constant speed running, for which energy costs were known.4 Then they used accelerations (transformed into equivalent slopes) in a previously reported regression equation for energy cost estimation during uphill and downhill running at constant speed.4 This method allows researchers to estimate energy cost via player accelerations, thus making energy estimations feasible in team sports matches.